Valley of bones [large type] - Richards, Dusty (Richards, Dusty. Byrnes family ranch., 2017)
"A landmark feat of innovation is about to change the American West. A new telegraph system will connect the settlers of the Arizona Territory to rest of the country--a dream come true for rancher Chet Byrnes and his family. But stretching four hundred miles of electric cable from the Colorado River to Gallup, New Mexico, can be a deadly task, and Chet has to deal with hired henchmen who would kill to sabotage the project. Then a pair of outlaws from Chet's past come seeking revenge that can only be paid with Byrnes family blood."--Back cover.